Human and animal exposure to newly discovered sand fly viruses, China - Yao, Xiaohui; Yin, Qikai; Tian, Xiaodong; Zheng, Yuke; Li, Hongyan; Fu, Shihong; Lian, Zhengmin; Zhang, Yijia; Li, Fan; Zhang, Weijia; He, Ying; Wang, Ruichen; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The Hedi virus (HEDV) and Wuxiang virus (WUXV) are newly discovered Bunyaviruses transmitted by sandflies. The geographical distribution of isolation of these two viruses continues to expand and it has been reported that WUXV causes neurological symptoms and even death in suckling mice. However, little is known about the prevalence of the two viruses in mammalian infections. Methods In order to understand the infection status of HEDV and WUXV in humans and animals from regions where the viruses have been isolated, this study used Western blotting to detect the positive rates of HEDV and WUXV IgG antibodies in serum samples from febrile patients, dogs, and chickens in the forementioned regions. Results The results showed that of the 29 human serum samples, 17.24% (5/29) tested positive for HEDV, while 68.96% (20/29) were positive for WUXV. In the 31 dog serum samples, 87.10% (27/31) were positive for HEDV and 70.97% (22/31) were positive for WUXV, while in the 36 chicken serum samples, 47.22% (17/36) were positive for HEDV, and 52.78% (19/36) were positive for WUXV. Discussion These findings suggest there are widespread infections of HEDV and WUXV in mammals (dogs, chickens) and humans from the regions where these viruses have been isolated. Moreover, the positive rate of HEDV infections was higher in local animals compared to that measured in human specimens. This is the first seroepidemiological study of these two sandfly-transmitted viruses. The findings of the study have practical implications for vector-borne viral infections and related zoonotic infections in China, as well as providing an important reference for studies on the relationship between sandfly-transmitted viruses and zoonotic infections outside of China.